(3TQM hbGjI GdQhGjI aj eSGFd GdgOGjIs - (3UOQ GdTQjYI GdKGfj, YHjO Gddg Hf eSYhO Hf JGL GdTQjYI eMehO GdeMHhHj, J (B747(3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; (B: (3GdMeO ddg QH GdYGdejf jbhd YHjO Gddg Hf eSYhO Hf JGL GdTQjYI gPG Md GdehGVY GdeZdbI ef hbGjI GdQhGjI ef eSGFd GdgOGjI GdJj CdagG LOj HQgGf GdTQjYI eMehO Hf UOQ GdTQjYIs
(3BNQgG (B:s
(3hdG VQhQI gfG bdfG GdJMQj jUGQ Edjg dOaY GdMQL hCShGb GdeSdejf dG JNdh ef GdeSQhb hGdeZUhH hGdeMQe heY Pdc ojHGM GdJfGhd GYJeGOG Ydi GdZGdHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 197s
(3eYLe GdeDdajf (B2 / 355s
(3cTa GdXfhf (B2 / 2021s
(3GdahGFO GdHgjI (B109s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs